ANALYSIS OF COMMUNITY AND GOVERNMENT READINESS IN FLOOD DISASTER MITIGATION IN JAWIK JEKULO KUDUS - Avina Imma Amalia; Najwatus Salma; Dany Miftah M. Nur (International Journal of Multidisciplinary Reseach, 2025)
This study aims to analyze the readiness of the community and government in flood disaster mitigation in Dukuh Jawik, Jekulo District, Kudus Regency. With the increasing intensity of rain due to climate change, the frequency of floods has also increased, causing significant impacts on people's lives, including access to education and health. The research method used was a qualitative survey, involving interviews with the community, village government, and literature studies to deepen understanding of flood patterns and their impacts. The results of the study indicate that synergy between the community and the village government is very important in disaster management. The community needs to increase awareness of flood risks and be involved in mitigation programs. On the other hand, the village government must provide adequate infrastructure and evaluate the effectiveness of existing structures, such as embankments and drainage channels. This study recommends the need for education and training for the community regarding disaster management and strengthening communication between the government and residents. With a collaborative approach, Dukuh Jawik can increase resilience to flood disasters and create a safer and more prosperous environment for all its residents.